2015
DOI: 10.1016/j.vetpar.2015.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Application of a body condition score index for targeted selective treatment in adult Merino sheep—A modelling study

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. AbstractThis study aimed to establish whether she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Recent investigations in Australia demonstrated that body condition score is a simple and practical indicator for a TST strategy in large flocks of adult sheep, and can be used to identify individual ewes at risk of compromised production or welfare if left untreated (Besier et al, 2010;Cornelius et al, 2014). These concluded that in Mediterranean environments, and where ewes are in good body condition, the random selection of wellconditioned ewes is a feasible and effective indicator of the sheep to leave untreated (Cornelius et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent investigations in Australia demonstrated that body condition score is a simple and practical indicator for a TST strategy in large flocks of adult sheep, and can be used to identify individual ewes at risk of compromised production or welfare if left untreated (Besier et al, 2010;Cornelius et al, 2014). These concluded that in Mediterranean environments, and where ewes are in good body condition, the random selection of wellconditioned ewes is a feasible and effective indicator of the sheep to leave untreated (Cornelius et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…Field investigations in Western Australia have confirmed that a TST strategy based on the selection of ewes for treatment (or otherwise) using body condition score is a practical procedure and does not jeopardise wool production when applied in adult sheep flocks in this environment (Besier et al, 2010), or adversely affect body weight or condition score (Cornelius et al, 2014;Cornelius et al, 2015b). However, field studies to determine the longer-term effects on the development of anthelmintic resistance and impacts on worm control effectiveness in the flock into the future are difficult and expensive to conduct in real time.…”
Section: Introductionmentioning
confidence: 99%